Roxadustat for Patients with Posttransplant Anemia: A Narrative Review - Xiaoxiao Tang; Fei Liu; Qiuyu Li; Jianhua Mao (Karger Publishers, 2023)
Background: Hypoxia-inducible factor-prolyl hydroxylase inhibitors (HIF-PHIs) are novel oral agents used for renal anemia treatment. Roxadustat, a first-in-class HIF-PHI used for treating anemia in chronic kidney disease patients, has been approved in China, Japan, South Korea, Chile, and Europe. Roxadustat is involved in HIF degradation, which can stimulate endogenous erythropoietin (EPO) production and improve iron utilization. Besides, roxadustat can promote dietary iron uptake and transport. In comparison with traditional erythropoiesis-stimulating agent treatment, it might reduce cardiovascular risk and mortality as it causes only a slight increase in the plasma EPO level. Phase II and III clinical trial reports have shown that roxadustat is effective for treating chronic kidney disease patients. The role of roxadustat in kidney transplant recipients (KTRs) needs to be examined as patients with chronic kidney disease are different from those receiving renal transplants. Summary: Clinical trials have demonstrated that roxadustat effectively increases and maintains hemoglobin levels in patients with dialysis-dependent and non-dialysis-dependent chronic kidney disease by stimulating endogenous EPO production and optimizing iron utilization. Roxadustat has recently been used effectively to treat patients with EPO-resistant anemia. It has also been used for treating patients with posttransplant anemia (PTA), which is a prognostic factor for mortality in KTRs with an iron deficiency and impaired glomerular filtration rate. Here, we examined the findings of four studies in a narrative review and discussed our perspectives regarding this field of study. Key Messages: Roxadustat significantly improves hemoglobin levels without affecting renal function in KTRs with PTA. It also enhances iron utilization by decreasing ferritin and hepcidin levels and increasing total iron binding capacity, transferrin, and serum iron levels. Roxadustat ameliorates anemia and inflammation, and might have reno-protective effects in KTRs.